An autonomous ultrasonic fastener holes inspection system of an aircraft lower wing skin - Lim, Chee Wei. (2008)
An aircraft structure is subjected to stress and fatigue during flying. Fasteners like rivets and bolts bear a large part of the stress and thus require frequent inspection for cracks around the fastener's holes. These cracks are unique in that it radial from the fastener's hole which made radiography nearly impossible in picking it up.